STUDI MEMBRAN KITOSAN DARI KULIT LOBSTER BAMBU SEBAGAI MEMBRAN FILTRASI - Putri Windari, Ni Nyoman; Rupiasih, Ni Nyoman; Sumadiyasa, Made (BULETIN FISIKA; Vol 17 No 1 (2016): BULETIN FISIKA, 2016)
The study of the extraction and characterization of chitosan from skin waste of Bamboo Lobster ( Panulirus versicolor) has been done. Chitosan is extracted using conventional method, namely the initial process: cleaning and drying (pretreatment), demineralization, deproteination, and deacetylation. The chitosan obtained has been used to prepare chitosan membrane 2% with acetic acid 1% as solvent. The membrane prepared by phase inversion method withprecipitation through solvent evaporation. The prepared membranes were characterized by FTIR spectrophotometer, Nova 1200e by BJH method and filtration method. The results obtained that degree of deacetylation (DD) of chitosan is 70.016%. The thickness of the membrane is 0.361 mm. The FTIR spectra show that functional groups obtained are -NH, -CH, C=O, C-O and -CN. From BJH method obtained that the pore radius is 1.69 nm and pore density is 8.95 x 10 5 pores/m 3 . From the filtration method obtained that at each pressure, 80-85 kPa and 90-100 kPa, the PWF values are 381.232 and 454.545 L/m 2 .h, respectively.